Design of Planar Sparse Antenna Array with Rectangular boundary by Bi-linear Approach - Zhang, Cheng; Qing, Anyong (Digest - IEEE Antennas and Propagation Society. International Symposium (1995), 2018)
A bi-linear approach is proposed to efficiently design planar sparse antenna arrays with rectangular boundary. On account of practical manufacturing and cost limitation, it deals with x-y de-coupled planar sparse arrays whose array factor could be decomposed into two linear array factors. Computational cost for both radiation pattern and array synthesis accordingly is significantly reduced. It is successfully applied to design an array with low sidelobe level.